Analytic modeling and large-scale experimental study of mass and heat transfer during hydrate dissociation in sediment with different dissociation methods - Wang, Yi; Feng, Jing-Chun; Li, Xiao-Sen; Zhang, Yu; Li, Gang (Energy, 2015)
An analytic model of the mass and heat transfers during hydrate dissociation in porous media by depressurization, thermal stimulation, and depressurization in conjunction with thermal stimulation without any empirical correlation is established in this work. Meanwhile, the PHS (Pilot-Scale Hydrate Simulator), a three-dimensional 117.8 L pressure vessel, is used for the investigation into the characteristics of the heat transfers and gas production behaviors during hydrate dissociation with the above dissociation methods. The model is solved analytically, and the predicted results are in good agreement with the experimental data. The results indicate that the sensible heat in porous media is firstly consumed for the hydrate dissociation, and then the heat transferred from the boundaries is employed for dissociating the hydrate in the reservoir by depressurization. The maximum deviations of the predicted gas production and the predicted temperatures with the model are 7.4% and 0.36%, respectively. With the thermal stimulation method, the maximum deviation of the predicted moles of the dissociated hydrate is 7.6%. There are two moving boundaries of the hydrate dissociation in the hydrate reservoir by depressurization in conjunction with heat stimulation. A synergistic effect of depressurization and heat stimulation on hydrate dissociation enhances the hydrate dissociation rates. (C) 2015 Elsevier Ltd. All rights reserved.